Dimensi Teologis Pujian dan Penyembahan dalam Eksorsisme: Analisis Kualitatif Pengalaman Pelayanan Pelepasan - Suwany, Suwany; Gidion, Gidion; Suwito, Gregorius (P3M STT Kristus Alfa Omega, 2025)
The potential of praise and worship as a strategic tool to face spiritual challenges is often overlooked in ministry practice. A deep and comprehensive understanding of the biblical principles underlying praise and worship is crucial to empowering the ministry. This study aims to explore the role of praise and worship in spiritual warfare and to understand the criteria that must be possessed in deliverance ministry. The research method used is descriptive qualitative, with data collection through interviews with ten data sources who have experience with praise and worship in deliverance ministry. The results of the study include praise and worship as an effective tool in facing the powers of darkness.